Das Fassadenuntergeschoss der Kathedrale San Rufino in Assisi Eine Untersuchung der architektonischen Gliederung und des dekorativen Repertoires - Wallbaum, Dorith (Universitätsverlag Göttingen, 2022)
The basement of the façade of the San Rufino at Assisi is part of the newly erected Cathedral, which can be dated between 1140 and about 1240. Its extensive décor shows the self-confidence of its sole initiators, the Canons of the Cathedral. On the one hand the present treatise is addressed at the differentiated planar structuring on behalf of a large-scaled framing with a salient arched corbel course and the debate of its derivation. Thereby the framing of the reliefs next to the main portal on the façade of San Pietro fuori le mura at Spoleto receives specific consideration, also in comparison with the different types of relief-framing of several churches in the southwestern Mediterranean area. On the other hand the diversified decorative repertoire of the façade-basement at Assisi is brought into focus in this treatise. In this context special attention is paid to the so far rudimentarily investigated motives of the presentations, their origin and distribution.